The impact of the COVID-19 epidemic on the utilization of dental services and attitudes of dental residents at the emergency department of a medical center in Taiwan - Ju-Hui Wu; Min-Kang Lee; Chen-Yi Lee; Nien-Hsiang Chen; Ying-Chun Lin; Ker-Kong Chen; Kun-Tsung Lee; Je-Kang Du (Elsevier, 2021)
Background/purpose: Dental visits are a high risk activity during the COVID-19 pandemic. This study investigated the utilization of emergency dental services and clinical practical attitudes of dental residents in this period. Materials and methods: Retrospective chart data from 13th November 2019 to 31st March 2020 in Kaohsiung Medical University Hospital, Taiwan were used. We obtained electronic medical records to review data from 515 patients who visited the emergency department with dental complaints and we contacted the 26 residents assigned to act as primary care providers to participate in this study. Results: After the COVID-19 outbreak, 17% fewer patients had dental emergency utilization at a hospital emergency center relative to the previous period. A survey of residents also showed a decline in the number of patients. There were no significant differences of patients' problems and diagnoses between the two periods. After the COVID-19 outbreak, 61.5% of the residents were afraid of being infected by a patient's disease and the proportions of dentists wearing waterproof gowns, face shields, and surgical hair caps were 76.9%, 88.5%, and 76.3%, respectively. These variables increased significantly after the outbreak of COVID-19. Conclusion: Despite the trend of a decreased number of patients, their utilization of dental emergency services seems to be similar before and after the COVID-19 outbreak, possibly related to strict hospital infection control policies and the relatively low number of COVID-19 confirmed patients internationally at that time.